E-009 A prospective, multicenter registry for the investigation of clot in ischemic stroke and hematoma evacuation: study protocol for insight. (4th August 2020) - Kellner, C; Fraser, J
Abstract : Introduction/Purpose: Multiple clinical studies have established the importance of effective clot evacuation on good clinical outcomes for acute ischemic and hemorrhagic stroke, and suggest that thrombus composition can impact treatment efficacy. Understanding clot composition and associated genomic, epigenomic, and proteomic signatures could provide insight into thrombus biology, etiology, and aid in prognosis. The primary objective of the INSIGHT study is to develop a 'multi-omic' blood clot signature to predict the etiology of the blood clot in patients with ischemic stroke or intracerebral hemorrhage (ICH). Clots retrieved through either mechanical thrombectomy or endoscopic ICH aspiration will be analyzed with histology, RNA sequencing, and proteomics while contemporaneously collected peripheral blood samples will undergo single nucleotide polymorphism (SNP) analysis, RNA sequencing, and proteomic analysis. A secondary objective is to identify specimen characteristics that correlate with patient clinical presentation, procedural outcome, hospital length of stay, and 90-day functional outcome. Materials and Methods: INSIGHT is a prospective, multicenter registry for the collection and analysis of specimens collected from ischemic stroke thrombectomy procedures and minimally invasive interventions for intracerebral hematoma evacuation utilizing the Penumbra Aspiration Pump. The registry will enroll up to 1000 patients from up to 50 U.S. sites. Patients age ≥18 years, treated frontline with the Penumbra System (for ischemic stroke patients eligible for mechanical thrombectomy) or the Artemis Neuro Evacuation device (for intracerebral hematoma evacuation in patients eligible for minimally invasive surgery), and with extracted thrombus/embolus, will be included. Exclusion criteria includes current participation in a clinical trial that may confound the ability to capture clot and/or influence clot composition. Patient demographics, medical history, procedural information, and extracted clot and blood specimen will be collected. Follow-up assessments will occur at discharge and at 90 days post-procedure. Results: The estimated date for study completion is 2023. Conclusion: We report the design of the INSIGHT study, a prospective 'multi-omic' registry to analyze specimen collected during ischemic stroke thrombectomy and minimally invasive intracerebral hematoma evacuation. Disclosures: C. Kellner: None. J. Fraser: None.